2022
DOI: 10.15835/nbha50112569
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the foliar application of potassium nanofertilizer on biomass, yield, nitrogen assimilation and photosynthetic activity in green beans

Abstract: The agricultural areas of the world face problems that create difficulties when producing food and the excessive use of fertilizers is generating a negative environmental impact. An alternative that appears as a solution to this problem is the use of nanofertilizers. Within nanofertilizers an area of opportunity is the application of macronutrients, which report an increase in absorption efficiency of 19% compared to conventional fertilizers. Potassium (K) is one of the three macronutrients most used in agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The application of K-NPs (200 mg/l) as splatter fertilizer has a salutary impact on onion plant development and production ( Table 3 , Table 4 ) in line with the study of Márquez-Prieto et al [ 7 ] that indicated that green bean plant production improved when treated with 200 ppm nano potassium, possibly due to increased cell split [ 51 ] and several enzymatic growth and activity to improve crop quality [ 52 ]. Potassium acts on the enzymes responsible for protein composition, sugar conversion, nitrogen and carbon metabolism, and photosynthesis, thereby enhancing plant productivity and quality [ 19 , 53 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The application of K-NPs (200 mg/l) as splatter fertilizer has a salutary impact on onion plant development and production ( Table 3 , Table 4 ) in line with the study of Márquez-Prieto et al [ 7 ] that indicated that green bean plant production improved when treated with 200 ppm nano potassium, possibly due to increased cell split [ 51 ] and several enzymatic growth and activity to improve crop quality [ 52 ]. Potassium acts on the enzymes responsible for protein composition, sugar conversion, nitrogen and carbon metabolism, and photosynthesis, thereby enhancing plant productivity and quality [ 19 , 53 ].…”
Section: Discussionsupporting
confidence: 74%
“…Fertilizers are typically used in food production to increase crop yield but can have detrimental ecological effects, so an alternative is the utilization of nano-fertilizers [ [6] , [7] , [8] ] which can boost absorption capacity by ∼19 % compared to traditional fertilizers [ 9 ] . Nano-fertilizers promote plant development and production [ 10 , 11 ], and are easily transported into cells due to their small size where they impact various metabolic and physiological processes [ 12 ] .…”
Section: Introductionmentioning
confidence: 99%
“…It might be because foliar application of N increases leaf N and chlorophyll content, and chlorophyll and leaf photosynthetic rate are closely related. Applying K nanofertilizer obtained a higher biomass accumulation, nitrate reductase activity, photosynthetic activity, SPAD values and total chlorophyll content [11]. Upadhyaya et al [12] and Thunugunta et al [13] reported identical comments.…”
Section: Resultsmentioning
confidence: 80%
“…Based on the findings obtained, it seems that the use of K nanofertilizers has a positive impact on the physiological growth of plants [73]. Drip irrigation with 75% nN and foliar treatment with 25% nN have a substantial effect on growth and biochemical parameters [74].…”
Section: The Effect Of Nanofertilizer On Crop Yieldmentioning
confidence: 99%